2018
DOI: 10.3892/or.2018.6346
|View full text |Cite
|
Sign up to set email alerts
|

GPNMB silencing suppresses the proliferation and metastasis of osteosarcoma cells by blocking the PI3K/Akt/mTOR signaling pathway

Abstract: Glycoprotein non‑metastatic melanoma protein B (GPNMB) is a glycoprotein that is highly expressed in various types of cancer, including osteosarcoma. However, its cellular functions and related mechanisms in osteosarcoma remain unclear. In the present study, a higher GPNMB mRNA level was observed in osteosarcoma tissues, than in adjacent non‑cancerous tissues. In addition, upregulation of the GPNMB mRNA and protein level was detected in the osteosarcoma cells SaOS2, 143B, MG63 and U2OS using western blot analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
(33 reference statements)
2
23
0
Order By: Relevance
“…Mice model of BMLC was made and treatment with SLBZ-AP was performed. Our data showed that SLBZ-AP Many researchers confirmed that PI3K/Akt/mTOR signaling pathway is related to a few biological activities to affect cell proliferation, survival, and migration [7,8], especially to stimulate proliferation, survival, invasion/metastasis, and metabolic reprogramming and suppress autophagy, which is involved in possible mechanisms of oncogenic transformation [9]. PI3K/Akt/mTOR signaling pathway is commonly activated and suppression of its activation may inhibit cells proliferation and metastasis in cancers of the lung [10,11,50], colorectal [51,52], esophagus [53], breast [54][55][56], liver [57,58], and kidney [59,60], which has been considered a promising therapeutic target.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Mice model of BMLC was made and treatment with SLBZ-AP was performed. Our data showed that SLBZ-AP Many researchers confirmed that PI3K/Akt/mTOR signaling pathway is related to a few biological activities to affect cell proliferation, survival, and migration [7,8], especially to stimulate proliferation, survival, invasion/metastasis, and metabolic reprogramming and suppress autophagy, which is involved in possible mechanisms of oncogenic transformation [9]. PI3K/Akt/mTOR signaling pathway is commonly activated and suppression of its activation may inhibit cells proliferation and metastasis in cancers of the lung [10,11,50], colorectal [51,52], esophagus [53], breast [54][55][56], liver [57,58], and kidney [59,60], which has been considered a promising therapeutic target.…”
Section: Discussionsupporting
confidence: 55%
“…It is necessary to find safe and effective drug therapies for BMLC currently. PI3K/Akt/mTOR signaling pathway plays a pivotal role in a variety of biological activities to regulate cell proliferation, survival, and migration [7,8]. e PI3K/AKT/mTOR axis commonly contributes to possible mechanisms of oncogenic transformation including stimulation of proliferation, survival, invasion/metastasis, and metabolic reprogramming, as well as suppression of autophagy [9].…”
Section: Introductionmentioning
confidence: 99%
“…PI3K activated its downstream molecule Akt, which lead to the phosphorylation and ultimately promotes tumour growth. This pathway was reported to serve as a critical role in many biological processes of tumours such as proliferation, migration and survival 15 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activation of Akt is highly implicated in lung metastasis. There are many reports showing that aberrant expression of proteins can active the PI3K/Akt signaling pathway facilitating the progression of OS [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] ( Figure 2 ). Intracellular adhesion molecule-1 (ICAM-1), a surface glycoprotein, takes part in cell–ECM adhesion and promotes metastasis in cancers [ 67 ].…”
Section: Signal Pathways In Os Metastasismentioning
confidence: 99%
“…Meanwhile, EMT, an important cellular process in cancer cell metastasis, is accelerated with the upregulation of Fibulin-4 [ 69 ]. The PI3K/Akt/mTOR signaling pathway is also active via the high expression of GPNMB and promotes OS cell metastasis and proliferation [ 70 ]. Transcription factors also take effect on the activation of PI3K/Akt such as overexpression of zinc finger transcription factor ZIC2, which can activate PI3K/Akt and promote the viability, migration, and invasion of OS cells [ 71 ].…”
Section: Signal Pathways In Os Metastasismentioning
confidence: 99%